EVALUASI MANAJEMEN WAKTU PROYEK MENGGUNAKAN METODE PERT DAN CPM PADA PENGERJAAN “PROYEK REPARASI CRANE LAMPSON” DI PT MCDERMOTT INDONESIA - Junafuji Oka; Dwi Kartikasari (Politeknik Negeri Batam, 2017)
Project scheduling is one of the elements of planning outcomes, which can provide information about project schedules and project progress in terms of resource performance in terms of cost, labor, equipment and materials and project duration plan with time efficiency for project completion. Critical Path Method (CPM) and Project Evaluation Review Technic (PERT) are two project scheduling methods that use different approaches in the process. In making a project, the researcher assumes that the initial success of a project should begin with the planning and preparation of the correct phase and the systematic stage